2017
DOI: 10.1002/bdr2.1176
|View full text |Cite
|
Sign up to set email alerts
|

Convergent neurobiological predictors of emergent psychopathology during adolescence

Abstract: The adolescent brain undergoes significant structural and functional development. Through the use of magnetic resonance imaging in adolescents, it has been demonstrated that the prefrontal cortex, pertinent for executive control, demonstrates protracted development compared to limbic structures, active during emotion and reward processing. This asynchronous development creates a sensitive window during adolescence, in which many psychopathological disorders (i.e. mental health and substance use) emerge. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 77 publications
(136 reference statements)
0
24
0
Order By: Relevance
“…increase in anxiety, depression, or other avoidance or withdrawal behaviors. Some have suggested that reduced volume and cortical thickness in frontolimbic regions may serve as a neurobiological predictors of emergent internalizing psychopathology in adolescence (Jones et al, 2017). However, others have observed delayed thinning in the ventromedial prefrontal cortex in high anxious children (Newman et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…increase in anxiety, depression, or other avoidance or withdrawal behaviors. Some have suggested that reduced volume and cortical thickness in frontolimbic regions may serve as a neurobiological predictors of emergent internalizing psychopathology in adolescence (Jones et al, 2017). However, others have observed delayed thinning in the ventromedial prefrontal cortex in high anxious children (Newman et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For example, delays in maturation associated with drug exposure, genetics, or social environment, may increase risky behaviors in adolescents 72 . Brain imaging studies have found altered structure of prefrontal cortices associated with higher risk for SUD in adolescents 73 , suggesting that control executive functions such as decision making and impulse control (inhibition) are immature 74 . Unfortunately, the neurobiological underpinnings of neuroadaptations for both functional development and SUD, are not fully understood, in part, by a high variability in VBM results 75 .…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…For example, delays in maturation associated with drug exposure, genetics, or social environment, may increase risky behaviors in adolescents 67 . Brain imaging studies have found altered structure of prefrontal cortices associated with higher risk for SUD in adolescents 68 , suggesting that control executive functions such as decision making and impulse control (inhibition) are immature 69 . Unfortunately, the neurobiological underpinnings of neuroadaptations for both functional development and SUD, are not fully understood, in part, by a high variability in VBM results 70 .…”
Section: Limitationsmentioning
confidence: 99%